A Hybrid Icebreaking Resistance Model to Accommodate Damage to the Ice Sheet - Bannish, David A (2013)
An analytical framework was constructed to interchange ice resistance components from existing ice resistance calculation methods. Within this framework, the Lindqvist analytical method bending ice resistance component was substituted with a value obtained from a finite element static model of the ice sheet. A parametric study of this substitution was performed with error correction to within 12% over the entire range of parameter variation. The finite element ice sheet model was then damaged; and then the average ice bending resistance was obtained, substituted into the Lindqvist analytical method, and quantified as a change in the total ice resistance. Therefore, a hybrid ice resistance model was developed that accounts for the effect of damage to the bending resistance component, and enables further study of unconventional icebreaking methods.